Socio-technical-economic assessment of power-to-X: Potentials and limitations for an integration into the German energy system. (May 2019) - Schnuelle, Christian; Thoeming, Jorg; Wassermann, Timo; Thier, Pablo; von Gleich, Arnim; Goessling-Reisemann, Stefan
Abstract: The German Energiewende is facing new challenges with increasing shares of fluctuating renewable energies. Slow electricity grid extensions, restrictions in public perception as well as limited transformation progress in other sectors beside electricity cause major drawbacks in greenhouse gas mitigation. Power-to-X (PtX) technologies may be the missing link for a more resilient energy transition and provide both, renewable substitutes for fossil fuels as well as electricity grid balancing services owing to flexible operation and long-term storage abilities. Different PtX concepts proved operability in several worldwide distributed pilot projects. However, little is known yet about potential technical, monetary, societal and resource related scale-up limitations. In this paper, implications of these aspects for a large-scale energy system implementation are shown. From a technical perspective the concept of long-term flexible PtX operation modes is generally feasible and could become key for a more resilient future energy supply. However, economics are still the bottleneck for an extensive diffusion: in two scenarios for 2050 PtX may cause additional national annual energy costs between approx. 10 and 100 billion euros compared to an ongoing fossil fuel supply at current price conditions. Nevertheless, such expenses can be considered as reasonable in contrast to expenses for the compensation of climate change consequences of a future fossil fuel-based energy system.